2016
DOI: 10.1002/eji.201445228
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor‐driven signals inhibit collagen synthesis in the gut

Abstract: Fibrostrictures (FS) are a major complication of Crohn's disease (CD). Pathogenesis of FS is not fully understood, but activation of fibroblasts and excessive collagen deposition are crucial in the development of FS. Here, we investigated the role of aryl hydrocarbon receptor (AhR) in intestinal fibrosis. AhR RNA and protein expression were evaluated in intestinal fibroblasts of CD patients and controls. CD fibroblasts were stimulated with TGF-β1 or TNF-α in the presence or absence of the AhR activator Ficz, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
3
32
1
Order By: Relevance
“…The AhR pathway is vital for tissue repair, including inflammation, angiogenesis, and ECM remodeling [16]. Recent studies have shown that AhR was associated with the remodeling process in many tissues, such as the gut [17], dermal fibroblasts [18], and lung cancer [19]. However, the role of AhR in tissue remodeling of CRS is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The AhR pathway is vital for tissue repair, including inflammation, angiogenesis, and ECM remodeling [16]. Recent studies have shown that AhR was associated with the remodeling process in many tissues, such as the gut [17], dermal fibroblasts [18], and lung cancer [19]. However, the role of AhR in tissue remodeling of CRS is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by this prior work, we tested if AhR signaling mediated therapeutic responses to STING agonists. Mice were given the AhR antagonist drug CH223191 (CH) at optimal doses (5 mg/kg) shown to block AhR signaling effectively in mice (30,(33)(34)(35). CH treatments were administered daily from EAE onset (day 11).…”
Section: Trp Depletion and Ahr Signaling Are Dispensable For Therapeumentioning
confidence: 99%
“…Signaling through AhR, a receptor for environmental toxins, can induce activation and proliferation of many cell types, such as fibroblasts ( 59 , 60 ). By selectively stimulating or inhibiting AhR on isolated fibroblasts from CD patients, Monteleone et al ( 61 ) have shown that AhR negatively regulates TNF-α- or TGF-β-driven collagen production, by affecting activation of NF-κB and Smad2/3, respectively. Moreover, they also demonstrated in vivo that specific stimulation of AhR in mice reduces the fibrosis associated with chronic long-term administration of TNBS in mice.…”
Section: Which Cytokines Are Important In Intestinal Fibrosismentioning
confidence: 99%